1999
DOI: 10.1021/bi991888a
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Inhibitor Design from the Crystal Structure and NMR Studies ofEscherichia coliGAR Transformylase in Complex with β-GAR and 10-Formyl-5,8,10-trideazafolic Acid,

Abstract: The crystal structure of Escherichia coli GAR Tfase at 2.1 A resolution in complex with 10-formyl-5,8,10-trideazafolic acid (10-formyl-TDAF, K(i) = 260 nM), an inhibitor designed to form an enzyme-assembled multisubstrate adduct with the substrate, beta-GAR, was studied to determine the exact nature of its inhibitory properties. Rather than forming the expected covalent adduct, the folate inhibitor binds as the hydrated aldehyde (gem-diol) in the enzyme active site, in a manner that mimics the tetrahedral inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(88 citation statements)
references
References 40 publications
(89 reference statements)
6
82
0
Order By: Relevance
“…An aspartate/histidine pair is found as a catalytic dyad or part of catalytic triad in the active site of a number of enzymes including serine proteases (16 -18), serine carboxypeptidase (19), phospholipase A 2 (20), dienelactone hydrolase (21,22), ribonuclease A (23), and a variety of zinc-dependent enzymes (24). From the group of 10-formyl-THF-converting enzymes, the GART mechanism and structure have been studied in more detail (15,(25)(26)(27) including resolution of several crystal structures of the enzyme (28 -31). It was shown that replacement of the conserved aspartate with asparagine resulted in catalytically inactive enzyme (15).…”
mentioning
confidence: 99%
“…An aspartate/histidine pair is found as a catalytic dyad or part of catalytic triad in the active site of a number of enzymes including serine proteases (16 -18), serine carboxypeptidase (19), phospholipase A 2 (20), dienelactone hydrolase (21,22), ribonuclease A (23), and a variety of zinc-dependent enzymes (24). From the group of 10-formyl-THF-converting enzymes, the GART mechanism and structure have been studied in more detail (15,(25)(26)(27) including resolution of several crystal structures of the enzyme (28 -31). It was shown that replacement of the conserved aspartate with asparagine resulted in catalytically inactive enzyme (15).…”
mentioning
confidence: 99%
“…The structure of GARF has been solved with various N-10-formyltetrahydrofolate analogues bound to the active site including the formylated analogue 10-formyl-5,8,10-tride-azafolic acid (NHS) (47). On the basis of the sequence and structure similarities between GARF and ArnA_TF described above, we modeled NHS in the active site of ArnA_TF using as a guide the position of NHS in GARF [PDB_ID 1C2T (47)].…”
Section: Substrate Binding Modelmentioning
confidence: 99%
“…This water molecule makes hydrogen bonds with O δ 1 of D 140 (2.9 Å), N δ 2 of N 102 (2.9 Å), and N δ 1 of H 104 (2.7 Å), the three residues implicated in the formyl transfer reaction ( Figure 4C). The main chain atoms of G 113 hydrogen bond with both the hydroxyl of the hydrated aldehyde of NHS [that represents where the primary amino group from the second substrate, UDP-Ara4N, would be (47)] and the side chain oxygen of the catalytically important D 140 bringing them together. Therefore, G 113 positions the amino group of UDP-Ara4N and the catalytic D 140 in a favorable conformation for catalysis.…”
Section: Substrate Binding Modelmentioning
confidence: 99%
“…GART is involved in the de novo synthesis of purines, catalysing the formylation of glycinamide ribonucleotide to formylglycinamide ribonucleotide in conjunction with the cofactor N"!-formyltetrahydrofolate (Buchanan & Hartman, 1959). Several of the residues identified as being important for the function of the E. coli version of GART (Almassy et al, 1992 ;Chen et al, 1992 ;Warren et al, 1996 ;Shim & Benkovic, 1999 ;Greasley et al, 1999) are present in the PvdF sequence (Fig. 3).…”
Section: Figmentioning
confidence: 99%
“…Positions where identical or similar residues are present in at least five of the sequences are highlighted, with identical residues shaded black and similar residues (A and G ; D and E ; F, W and Y ; I, L, M and V ; N and Q ; S and T ; H, R and K) shaded grey. Residues that are known to be involved in catalysis by GART from E. coli (Warren et al, 1996 ;Shim & Benkovic, 1999) are marked with an asterisk, and those that form a hydrophobic pocket and are likely to interact with formyl tetrahydrofolate (Almassy et al, 1992 ;Chen et al, 1992 ;Greasley et al, 1999) are marked with a dagger.…”
Section: Involvement Of Pvdf In Pyoverdine Synthesismentioning
confidence: 99%